The Effect of Reading Intensity on Perception of Sara Issues Frame News Tolikara Papua 17 July 2015 - Rizki Hidayat (INJECT (Interdisciplinary Journal of Communication), 2022)
This study aims to explain the effect of the intensity of reading news at metrotvnews.com on the attitude of the reader, to clarify the attitude of the reader toward reader perception of the news of Tolikara, Papua 17 Juli 2015. One of the factors that influence the credibility of the media is the intensity of journalists in reporting news. The effect of uncertainty of the news will make ambiguity in public perception. Data were obtained from 100 populations, using the nonprobability sampling technique model of purposive sampling. The results showed that the intensity of reading news on Metrotvnews.com had an effect of 0.327 or 32.7% on reader attitudes. The reader's perspective affects the reader's perception of the Tolikara news frame by 0.546 or 54.6%. Readers' attitudes modulate the impact of news intensity on readers' perceptions by 0.375, or 37.5%. This study concludes that cyber media still have an impact on agenda setting against the reader. Proved there is a significant relationship between the intensity of reading news and reader attitude to reader perception, it can be said that the longer individuals are exposed to an issue, so people will be affected by the agenda setting. Therefore the media in covering the news must be impartial (covering both sides) and the principle of neutrality in the preparation of news.